Comparison of Efficiency Measurement Techniques for Electric Vehicle Traction Inverters - Acar, Fatih; Ozdemir, Sadik; Akca, Hakan; Selamogullari, Ugur Savas (IEEE, 2015)
Performance evaluation of a high-resolution computer based efficiency measurement system for electric vehicle (EV) traction inverter is given. First, a simulation study is carried out to determine the upper limit of the EV traction inverter efficiency curve. Then, experimental efficiency measurements are completed. In the experimental study, a 30kVA induction machine-dynamometer system is used to obtain the loading between 1kW-8kW. Efficiency measurements are completed with both the YOKOGAWA WT500 power analyzer and the proposed computer based efficiency measurement system. Results are discussed and compared considering the accuracy and the cost.
Keywords: Electric vehicle; Efficiency measurement; Inverter; Computer Science; Engineering